Dynamic ReLU - Chen, Yinpeng; Dai, Xiyang; Liu, Mengchen; Chen, Dongdong; Yuan, Lu; Liu, Zicheng (16th European Conference Computer Vision (ECCV 2020), 2020)
Rectified linear units (ReLU) are commonly used in deep neural networks. So far ReLU and its generalizations (non-parametric or parametric) are static, performing identically for all input samples. In this paper, we propose Dynamic ReLU (DY-ReLU), a dynamic rectifier of which parameters are generated by a hyper function over all input elements. The key insight is that DY-ReLU encodes the global context into the hyper function, and adapts the piecewise linear activation function accordingly. Compared to its static counterpart, DY-ReLU has negligible extra computational cost, but significantly more representation capability, especially for light-weight neural networks. By simply using DY-ReLU for MobileNetV2, the top-1 accuracy on ImageNet classification is boosted from 72.0% to 76.2% with only 5% additional FLOPs.